2015
DOI: 10.4103/2230-8229.149588
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the nutritional status of the elderly and its correlates

Abstract: Background:The percentage of elderly is growing rapidly and malnutrition is not uncommon in the elderly.Objectives:The present study was carried out to assess the nutritional status of the elderly using the Mini Nutritional Assessment (MNA) tool, and to study the various epidemiological factors influencing their nutritional status.Materials and Methods:This cross-sectional study was done from July 2012 to August 2013 in Boko-Bongaon Block, Kamrup District, Assam, India. The elderly, those over 60 years of age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
98
11
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(163 citation statements)
references
References 9 publications
(12 reference statements)
22
98
11
2
Order By: Relevance
“…As seen in studies conducted in other countries in the region (14,16,17) an increasing age is found to be independently associated with poor nutritional status in our study too. Aging is associated with the decline in a number of physiological functions that can impact nutritional status, including impaired digestion, difficulties in chewing and swallowing, loss of sensory perception, and impaired metabolism (1,5,6).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…As seen in studies conducted in other countries in the region (14,16,17) an increasing age is found to be independently associated with poor nutritional status in our study too. Aging is associated with the decline in a number of physiological functions that can impact nutritional status, including impaired digestion, difficulties in chewing and swallowing, loss of sensory perception, and impaired metabolism (1,5,6).…”
Section: Discussionsupporting
confidence: 72%
“…This finding is somewhat low compared to the observed findings in the region; in an Indian study the rate was 60.4% and in an Iranian study conducted on the elderly living in nursing homes the rate was 38.7% (12,13). Further, no gender difference in the rate of malnutrition was observed in our study although many studies conducted on nutritional status of elders in South Asia had shown gender differences of nutritional status in the elderly (12)(13)(14). For example, a study conducted in Assam, India (14) found that the elderly women were at higher risk of being malnourished compared to the elderly men (45.6% vs 21.7%).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations